Strength exercises influence on functional capacities in mountain biking - Ionut, B. M. (Journal of Social Science, 2019)
Force in resistance regime is specific for those branches in which the student has to face a great resistance effort amplified not only by the distance size and its traversed duration, but also by the peculiarities of going onward, performance of mechanical work (water density and consistency of shoe layer, complexity of road) required by the competition and implicitly preparing (swimming, kayak-canoe, rowing, speed skating, cross-country skiing, cycling). Physical training of cyclist represents a process of educating physical quality. Each type of cycling imposes specific requirements in relation to physical training level of a sportsman.